Analisis Perbedaan Pengaruh Mc Kenzie exercise dan Post Isometric Relaxation terhadap Penurunan Nyeri Leher Non Spesifik pada Remaja - Putri, Nabila Ayu Meilya; Zuhri, Saifudin; -, Sugiono (UI Scholars Hub, 2026)
Background: The use of laptops and computers has become an essential part of daily life, especially among adolescents. However, the habit of maintaining a static posture for prolonged periods while using these devices often leads to excessive strain on the neck and shoulder muscles. To address these problems, interventions such as Mc Kenzie exercise and post isometric relaxation can be applied. Objective: To determine the difference in the effects of Mc Kenzie exercise and post isometric relaxation on reducing nonspecific neck pain in adolescents. Methods: This study employed a two-group pre and post-test design conducted from June to July 2025 at SMAN 1 Pulung Ponorogo. Subjects were selected using simple random sampling, with a total of 30 participants. Group I received Mc Kenzie exercise, while Group II received post isometric relaxation. Each group underwent treatment twice a week for four weeks. Pain intensity was measured before the first session and after the eighth session using the visual analogue scale (VAS). Results: Statistical analysis using paired t-tests showed significant differences in both Group I (p=0.001, pConclusion: Both Mc Kenzie exercise and post isometric relaxation effectively reduced nonspecific neck pain. However, post isometric relaxation was found to be more effective in reducing pain compared to Mc Kenzie exercise.